Increased risk of postoperative in‐hospital complications after radical prostatectomy in patients with prior organ transplant. Issue 16 (13th September 2021) - Wenzel, Mike; Würnschimmel, Christoph; Chierigo, Francesco; Tian, Zhe; Shariat, Shahrokh F.; Terrone, Carlo; Saad, Fred; Tilki, Derya; Graefen, Markus; Banek, Severiné; Kluth, Luis A.; Mandel, Philipp; et al.
Abstract: Background: To analyze postoperative, in‐hospital, complication rates in patients with organ transplantation before radical prostatectomy (RP). Methods: From National Inpatient Sample (NIS) database (2000–2015) prostate cancer patients treated with RP were abstracted and stratified according to prior organ transplant versus nontransplant. Multivariable logistic regression models predicted in‐hospital complications. Results: Of all eligible 202, 419 RP patients, 216 (0.1%) underwent RP after prior organ transplantation. Transplant RP patients exhibited higher proportions of Charlson comorbidity index ≥2 (13.0% vs. 3.0%), obesity (9.3% vs. 5.6%, both p < 0.05), versus to nontransplant RP. Of transplant RP patients, 96 underwent kidney (44.4%), 44 heart (20.4%), 40 liver (18.5%), 30 (13.9%) bone marrow, <11 lung (<5%), and <11 pancreatic (<5%) transplantation before RP. Within transplant RP patients, rates of lymph node dissection ranged from 37.5% (kidney transplant) to 60.0% (bone marrow transplant, p < 0.01) versus 51% in nontransplant patients. Regarding in‐hospital complications, transplant patients more frequently exhibited, diabetic (31.5% vs. 11.6%, p < 0.001), major (7.9% vs. 2.9%) cardiac complications (3.2% vs. 1.2%, p = 0.01), and acute kidney failure (5.1% vs. 0.9%, p < 0.001), versus nontransplant RP. In multivariable logistic regression models, transplant RP patients were at higher risk of acute kidney failure (odds ratio [OR]: 4.83), diabetic (OR: 2.81), major (OR: 2.39), intraoperative (OR: 2.38), cardiac (OR: 2.16), transfusion (OR: 1.37), and overall complications (1.36, all p < 0.001). No in‐hospital mortalities were recorded in transplant patients after RP. Conclusions: Of all transplants before RP, kidney ranks first. RP patients with prior transplantation have an increased risk of in‐hospital complications. The highest risk, relative to nontransplant RP patients appears to acute kidney failure.